TAFSIR VS HERMENEUTIKA: SEBUAH STUDI KOMPARASI - Sulhadi, Asep (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2018)
Every religion has a religious book, and every religious book has its own history and traditions of understanding. The era of globalization that blows from the West brings the spirit of eliminating boundaries and seeking equality of things. One effect is the emergence of some people's understanding to make hermeneutics a substitute for interpretation.Is it true that the Quran needs hermeneutics? Can tafseer be replaced by hermeneutics? Are there any similarities or differences between interpretations and hermeneutics? These are the things that I will discuss in this simple study.Keywords: tafseer, hermeneutics, qur’an, interpretation